From Agility to Achievement: How Work Agility and Job Crafting Drive Millennial Civil Servants’ Performance Through Learning Agility and Organizational Support - Aris Triyono; Tomy Fitrio; Raja Marwan Indra Saputra (Journal of Economics and Management, 2026)
This study develops and tests a conceptual model examining the relationships between work agility, job crafting, and the performance of millennial civil servants, incorporating learning agility as a mediator and perceived organizational support as a moderator. A cross-sectional survey was conducted among 137 millennial civil servants in Indragiri Hulu Regency using a 5-point Likert scale questionnaire. Data were analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 4.1. The results indicate that both work agility and job crafting positively influence performance, with learning agility partially mediating these effects. Additionally, perceived organizational support moderates the relationships between work agility, job crafting, learning agility, and performance. Unlike previous studies that primarily focus on structural or bureaucratic factors, this research emphasizes the unique characteristics and work dynamics of the millennial generation. This study addresses a research gap by integrating work agility, job crafting, learning agility, and perceived organizational support into a single, comprehensive model that has rarely been examined simultaneously among civil servants. Theoretically, the study extends the Job Demands–Resources (JD–R) Theory by demonstrating the mediating role of learning agility and the moderating role of perceived organizational support in strengthening the relationship between job resources and employee performance in a public sector setting. These findings are consistent with the Job Demands–Resources (JD–R) Theory, highlighting the critical role of both individual and organizational resources in enhancing civil servants' performance.